PENGARUH ECONOMIC VALUE ADDED (EVA) DAN MARKET VALUE ADDED (MVA) TERHADAP RETURN SAHAM PADA SEKTOR HEALTHCARE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Sugiharto Sugiharto; Rizal Efendi; Baidowi Abdhie (Fakultas Ekonomi Universitas Tridinanti Palembang, 2022)
This study aims to: (1). Knowing and analyzing the effect of Economic Value Added (EVA) on stock returns in healthcare companies listed on the Indonesia Stock Exchange for the 2017-2021 period. (2). Knowing and analyze the effect of Market Value Added (MVA) on stock returns in healthcare companies listed on the Indonesia Stock Exchange for the 2017-2021 period. (3) Knowing and analyzing the effect of Economic Value Added and Market value Added together on stock returns in healthcare companies listed on the Indonesia Stock Exchange for the 2017-2021 period.The research design used is causality research design with associative problem formulation. That is testing the influence between the independent variable and the dependent variable. The research population is the Financial Statements of Healthcare companies listed on the Indonesia Stock Exchange for the period 2017-2021. By demonstrating purposive sampling technique through consideration criteria so that the sample obtained is 13 Healthcare Company Financial Statements. The analysis technique used is multiple linear regression analyses, where before being tested, the classical assumption test is carried out with the help of the Statistical for product and service solution (SPSS Ver. 25). The results show that the Economic Value Added has no significant effect on stock returns. Market Value Added shows the results cause a significant effect on stock returns. As one, the effect of economic value added and market value added on stock returns is 18.2%. The rest is influenced by other variables not examined in this study. Key Word: Economic Value Added (EVA), Market Value Added (MVA) and Stock Return